(untitled) (Medical Forum Monthly, 2021)
Objective: To determine the outcomes of PCNL (multitract percutaneous nephrolithotomy) in patients presented with renal staghorn calculus. Study Design: Descriptive case series study. Place and Duration of Study: This study was conducted at the Department of Urology Saidu Teaching Hospital Swat and PIMS Islamabad, during from the period December 2018 to December 2019. Materials and Methods: Two hundred and ten patients of both genders with renal staghorn calculi of >20 mm in size were included. Patients detailed demographics were recorded after taking written consent. Multiple tract PCNL was done after completion of all investigations. All patients were given prophylactic antibiotics. Stone clearance post-operatively was assessed by CT-KUB. Follow-up was taken at 1 month postoperatively. Data was analyzed by SPSS 24.0. Results: There were 100 (47.62%) males while 110 (52.38%) were females. Mean age of 42.26±12.68 years. Mean BMI was 24.68±2.13 kg/m2. Mean size of the stone was 24.88±4.73 mm. Postoperative complications found in 40 (19.05%) patients, in which 20 (9.52%) patients had fever, blood transfusion in 8 (3.81%) patients, wound infection in 6 (2.86%), hydrothorax in 4 (1.90%) patients and 2 (0.95%) patient had septic shock. Overall stone clearance rate with multiple tract PCNL was 87.92%. Conclusion: It is concluded that multitract PCNL is safe and very effective treatment modality for staghorn caculi with higher stone clearance rate and fewer postoperative complications.